'Buy British': An analysis of UK attempts to turn a slogan into government policy in the 1970s and 1980s. Issue 7 (28th September 2022) - Clayton, David; Higgins, David M.
Abstract: This article uses newly available state and business records to investigate the effectiveness of Buy British policies when Britain was a member of the EEC between the early 1970s and the mid-1980s – a period of rapid import penetration and deindustrialisation. We show that government pursued a range of overt and covert measures to combat these economic problems. Overt measures sought to encourage domestic consumers to buy British; covert measures, involving nationalised industries and public procurement, attempted to encourage British firms to source domestically. The article contributes to the emerging business history literature on how Member States tried to exploit loopholes in EEC competition and commercial policy, and it provides new evidence on UK consumer preferences for domestic and imported manufactures.